2-Methoxynaphthalene acylation using aluminum or copper salts of tungstophosphoric and tungstosilicic acids as catalysts - Mendez, Leticia Jesica (2011)
Aluminum or copper salts of the tungstophosphoric (TPA) and tungstosilicic (TSA) acids were synthesized. They present interesting characteristics as catalysts because they can have Lewis and/or Brønsted acidity. The salts were characterized by Fourier transform infrared (FT-IR) spectroscopy, measurement of the specific surface area BET, X-ray diffraction, differential scanning calorimetry (DSC) and estimation of the acidity by potentiometric titration with n-butylamine. The salts keep the Keggin structure of the [PW12O40]3− and [SiW12O40]4− heteropolyanions intact during the synthesis. The salts of TPA are thermally more stable than those of TSA. All the salts showed very strong acid sites by potentiometric titration, the acid strength and the number of acid sites being higher for the Al3+ salts. The salts also showed an excellent catalytic behavior in the reaction of 2-methoxynaphthalene acylation with acetic anhydride. The aluminum salts led to better yields, which are correlated with their higher acidity. Also, it was observed that the solvent nature has an effect on the attained conversion.